Analisis Kecerdasan Musikal Anak Usia Dini dalam Kegiatan Bermain Drum Band di TK Negeri Alternatif Balige - Basha Gratia Simarmata; Anada Leo Virganta (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
This research uses qualitative methods. The aim of this qualitative research is to explain the musical intelligence of young children when playing drumband at the Balige Alternative Kindergarten. This research involved three teacher trainers and twenty early childhood children at Alternafif Balige Kindergarten. This research uses observation and interviews to collect data, and then carries out data analysis such as collecting, reducing, conveying, and drawing conclusions. The results of the research show that the musical intelligence of young children at the Balige Alternative Kindergarten develops well during drum band playing activities.